Lipid remodeling of contrasting maize (Zea mays L.) hybrids under repeated drought - Kränzlein, Markus; Schmöckel, Sandra M.; Geilfus, Christoph-Martin; Schulze, Waltraud X.; Altenbuchinger, Michael; Hrenn, Holger; Roessner, Ute; Zörb, Christian (Frontiers in Plant Science, 2023)
The role of recovery after drought has been proposed to play a more prominent role during the whole drought-adaption process than previously thought. Two maize hybrids with comparable growth but contrasting physiological responses were investigated using physiological, metabolic and lipidomic tools to understand the plants’ strategies of lipid remodeling in response to repeated drought stimuli. Profound differences in adaptation between hybrids were discovered during the recovery phase of lipidomic adaptation, which likely gave rise to different degrees of lipidomic adaptability to the subsequent drought event. These differences in adaptability are visible in galactolipid metabolism and fatty acid saturation patterns during recovery and may lead to a lipidomic dysregulation in the sensitive maize hybrid. Moreover, the more drought tolerant hybrid displays more changes of metabolite and lipid abundance with higher number of differences within individual lipids, despite of a lower physiological response, while the responses in the sensitive hybrid are higher in magnitude, but lower in significance on the level of individual lipids and metabolites. This study suggests that lipid remodeling during recovery plays a key role in the drought response of plants.